Skeletal Radiology - Chalian, Majid (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Musculoskeletal (MSK) disorders are among the top five contributors to disability-adjusted life years (DALYs) worldwide. These disorders include a wide range of conditions, spanning from fractures, sports injuries, rheumatoid arthritis, and musculoskeletal pain syndromes to those mostly affecting older age groups like osteoarthritis and osteoporosis. MSK conditions often present diagnostic challenges due to overlapping symptoms, complex anatomical aspects, and the variety of potential causes. Imaging plays a pivotal role in diagnosing and guiding treatment for these disorders. In the past decade, the MSK radiology field has witnessed significant progress driven by breakthroughs in artificial intelligence (AI), the development of high-resolution equipment and novel imaging sequences, and the adoption of innovative multidisciplinary approaches. This Special Issue on skeletal radiology brings together a diverse collection of articles that showcase the latest advancements in this field. From evaluating flatfoot to exploring emerging targets for osteoarthritis treatment, the included studies provide valuable insights into diagnostic accuracy and the expanding applications of skeletal radiology techniques. This editorial aims to highlight the significance of these articles and their contributions to the field of skeletal radiology.